Body Dissatisfaction Among Sexual Minority Men: Psychological and Sexual Health Outcomes - Blashill, Aaron J. (Arch Sex Behav, 2016)
Body dissatisfaction is common among sexual minority (i.e., gay and bisexual) men; however, few studies have investigated the relationship between body dissatisfaction and psychosexual health variables among this population. The data that do exist are exclusively cross-sectional, casting uncertainty regarding temporal associations. Thus, the aims of the current study were to assess the prospective relationship between body dissatisfaction and psychological and sexual health outcomes. Participants were 131 gay and bisexual men who completed a battery of self-report measures across two time points (baseline and 3-month follow-up), including assessment of body dissatisfaction, depressive symptoms, and sexual health variables (sexual self-efficacy and sexual anxiety). Generalized linear modeling was employed to assess the prospective relationship between body dissatisfaction and outcomes variables, accounting for non-normal distributions. Body dissatisfaction significantly predicted elevated depressive symptoms (B = .21, p = .01), lower sexual self-efficacy (B = −.22, p = .04), and elevated sexual anxiety (B = .05, p = .03). Elevated body dissatisfaction is prospectively associated with negative psychological and sexual health outcomes. Given the high prevalence of body image concerns in sexual minority men, depression and/or HIV/STI prevention programs may benefit from routinely assessing for body dissatisfaction among this population, and addressing those who report concerns.